84.1k views
4 votes
4x-(8-x)-2= 9x - 20+x-5​

User Jtate
by
5.6k points

1 Answer

1 vote

Answer:

Let's solve your equation step-by-step.

4x−(8−x)−2=9x−20+x−5

Step 1: Simplify both sides of the equation.

4x−(8−x)−2=9x−20+x−5

4x+−8+x+−2=9x+−20+x+−5

(4x+x)+(−8+−2)=(9x+x)+(−20+−5)(Combine Like Terms)

5x+−10=10x+−25

5x−10=10x−25

Step 2: Subtract 10x from both sides.

5x−10−10x=10x−25−10x

−5x−10=−25

Step 3: Add 10 to both sides.

−5x−10+10=−25+10

−5x=−15

Step 4: Divide both sides by -5.

Answer:

x=3

hope this helps (>'-'<)

User Noev
by
6.3k points